Reducing industrial energy costs through energy efficiency measures in the South African foundry industry - evaluation and opportunities of a South African foundry - Thiel, Dennis (Energy Research Centre, 2017)
Due to lack of generation capacity and high energy intensities South Africa's electricity supplier is forced to shut down high energy users frequently. Power cuts as well as escalating electricity prices threaten the country's steel industry. The objective of this study was to identify cost-effective energy efficiency improvements for the South African foundry industry. A lack of research in South African foundries was identified as existing literature on the topic was analysed. A large foundry operating an induction furnace in the Western Cape served as subjects to investigate the topic specifically in South Africa. The aim was to identify the energy intensity, evaluate already implemented energy efficiency measures and identify further opportunities to reduce energy cost of the foundry. The method followed for the data collection was much orientated on an industry energy audit. Types of energy, amounts and cost of energy usage were determined. The energy consumption and energy intensity of the foundry were analysed, based on meter readings, electricity bills and where necessarily a "bottom-up" approach for estimation was used. Results of the energy audit have shown that the foundry under review consumes about 127,000 MWh annually with a maximum demand of 26,500 kVA. The already implemented energy saving measures decreased the company's energy usage by 5% resulting in a current energy intensity of 1,493ZAR/ton. Further proposed energy efficiency measures included the compressed air system, preheating of the charge material and the reduction of the holding furnaces were analysed. The results of all evaluated measures, namely lighting, load-shifting and maximum demand management were cost effective solutions. Furthermore the recommended energy efficiency measures, namely reduction of compressed air leaks, reduction of holding furnaces as well as preheating of charge material, showed in theoretical calculations a reduction of carbon emissions as well as cost savings. This study offers an insightful view on energy intensity and energy efficiency opportunities in South African foundries, especially the ones operating an induction furnace.